2006
DOI: 10.1021/ol0606536
|View full text |Cite
|
Sign up to set email alerts
|

A New Modular Indole Synthesis. Construction of the Highly Strained CDEF Parent Tetracycle of Nodulisporic Acids A and B

Abstract: [reaction: see text] Construction of the highly strained CDEF parent tetracycle, a structural motif found only in the potent ectoparasiticidal agents (+)-nodulisporic acids A and B and related congeners, has been achieved via a new modular indole synthesis, exploiting a sequential Stille cross-coupling/Buchwald-Hartwig union/cyclization tactic. The new indole synthesis holds the promise of rapid assembly of diverse, highly substituted indoles possessing uncommon substitution patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Synthesis of the requisite cyclization precursors 1-3 was accomplished through a Stille coupling reaction between an ortho-substituted arene and vinyl stannane utilizing Pd(PPh 3 ) 4 or Pd 2 dba 3 /tri(2-furyl)phosphine with excess CuI in NMP. [20] Preliminary investigation and optimization of the cyclization centered on three substrates to determine the feasibility of this methodology. In a screen of cyclization conditions, treatment of 1 with 10 mol% of (8S, 9R)-N-benzylcinchonidinium chloride 7 in toluene with either aqueous K 2 CO 3 or solid Cs 2 CO 3 returned only starting material (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of the requisite cyclization precursors 1-3 was accomplished through a Stille coupling reaction between an ortho-substituted arene and vinyl stannane utilizing Pd(PPh 3 ) 4 or Pd 2 dba 3 /tri(2-furyl)phosphine with excess CuI in NMP. [20] Preliminary investigation and optimization of the cyclization centered on three substrates to determine the feasibility of this methodology. In a screen of cyclization conditions, treatment of 1 with 10 mol% of (8S, 9R)-N-benzylcinchonidinium chloride 7 in toluene with either aqueous K 2 CO 3 or solid Cs 2 CO 3 returned only starting material (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The ester 4 was then transformed into hydrazone 5 by reacting it with N -aminoindoline in methanol. N -Aminoindoline was prepared from commercially available indoline via a nitrosation–reduction sequence . In the next step, the ester group of 5 was converted into the corresponding phosphonate by reacting it with deprotonated methyl dimethylphosphonate in THF at −78 °C .…”
Section: Resultsmentioning
confidence: 99%
“…36 A related intramolecular amination reaction between an aniline and an alkenyl triflate was employed by Smith and co-workers in their synthesis of the nodulisporic acids tetracycle. 37 The Willis research group also demonstrated that similar palladium-catalyzed cascade processes can be achieved using pyridine-derived substrates to provide access to the corresponding azaindole products. 35e For example, reaction of dihalopyridine substrate 24 with p-anisidine, using a DPEPhos-derived catalyst, delivered the corresponding 7-azaindole in good yield (Scheme 9).…”
Section: %mentioning
confidence: 99%